Whole-genome analysis for backfat thickness in a tropically adapted, composite cattle breed from Brazil - Veneroni-Gouveia, G.; Meirelles, S. L.; Grossi, D. A. [UNESP]; Santiago, A. C.; Sonstegard, T. S.; Yamagishi, M. E. B.; Matukumalli, L. K.; Coutinho, L. L.; Alencar, M. M.; Oliveira, Henrique Nunes de [UNESP]; Regitano, L. C. A. (Wiley-Blackwell, 2012)
Backfat thickness affects the preservation of the beef carcass after slaughter and confers organoleptic characteristics assessed by the consumer. One of the breeding goals for Canchim, a tropically adapted breed, is to comprehensively increase fat thickness. Our goals were to identify genomic regions associated with backfat in Canchim populations and validate the association of single nucleotide polymorphisms (SNPs) overlapping previously identified QTL regions known to affect fat deposition. Fifteen animals with lower and 15 animals with higher residues for backfat, according to a linear model using the SAS GLM procedure, were selected from a population of 1171 animals and genotyped using the BovineSNP50 BeadChip. Initial analysis revealed more than 100 SNPs that discriminated the tails of phenotypic distribution. One extended region of association included the centromeric region of chromosome (Chr) 14. Because this region overlapped with QTL from previous reports, we developed SNP assays to interrogate two linkage disequilibrium blocks, one in the centromeric region and another in the middle region of Chr 14 to confirm the association. The analysis validated the presence of specific haplotypes affecting fat thickness.
Keywords: Fat deposition; single nucleotide polymorphism; tropically adapted cattle